2010
DOI: 10.1364/ol.35.003204
|View full text |Cite
|
Sign up to set email alerts
|

Six-cycle mid-infrared source with 38 μJ at 100 kHz

Abstract: We report on the shortest pulses to date from a mid-IR optical parametric chirped pulse amplification: 67 fs duration with 3.8 μJ energy operating at 3.2 μm. The system is all solid state and diode pumped and operates at 100 kHz with unprecedented power stability of 0.75%rms over 30 min.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 13 publications
0
27
0
1
Order By: Relevance
“…High-energy pump and seed for OPA eventually relies on CPA schemes followed by nonlinear spectral broadening [15,16]. However, access to the long MIR wavelengths has been limited due to the nearly exclusive use of near-infrared (NIR) pump sources at 800 nm and 1 μm [17]. Moreover, accessing long MIR wavelengths (>5 μm) requires OPAs based on non-oxide crystals, as most oxide crystals are either not transparent above 4-5 μm or have very low conversion efficiency [18] with a NIR pump.…”
Section: Introductionmentioning
confidence: 99%
“…High-energy pump and seed for OPA eventually relies on CPA schemes followed by nonlinear spectral broadening [15,16]. However, access to the long MIR wavelengths has been limited due to the nearly exclusive use of near-infrared (NIR) pump sources at 800 nm and 1 μm [17]. Moreover, accessing long MIR wavelengths (>5 μm) requires OPAs based on non-oxide crystals, as most oxide crystals are either not transparent above 4-5 μm or have very low conversion efficiency [18] with a NIR pump.…”
Section: Introductionmentioning
confidence: 99%
“…The calculation shows that a bandwidth of 43 THz (−10 dB) centered at 3.5 μm can be obtained with negligible angular dispersion (200 μrad across the full amplification bandwidth). The transform-limited pulse duration of such a bandwidth is 19 fs (1.6cycle), more than a factor of 2 shorter than the state-of-the-art, 1 μm pumped, 3-5 μm OPCPA pulses [9,10].…”
mentioning
confidence: 97%
“…We identify the potential of the scheme to generate a broadband 3.5 μm idler, with a bandwidth supporting a sub-two-cycle pulse. Due to the lack of mid-IR laser media, differencefrequency generation or optical parametric amplification (OPA) have been largely employed to down-convert visible or near-IR light sources [7][8][9][10]. It has been shown that mid-IR crystals such as LiIO 3 , KNbO 3 , and MgO:LiNbO 3 have group-velocity matched wavelengths, when pumped at 800 nm, between 950 nm and 1050 nm, and thus allow the direct generation of a broadband mid-IR idler with spectra supporting three-cycle pulses [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…138,139 Indeed, NIR OPCPA sources have demonstrated that they can directly produce amplified few-cycle pulses as short as 5.5 fs 140 and have already been reported at 2.1 µm 141 and in the mid-IR at 3.2 µm. 142 The novel design of the latter OPCPA directly produces CEP stable pulses and allows self-compression to sub-3-cycle duration by nonlinear propagation in the anomalous dispersion regime in dielectric media. 42 Another interesting approach to ultra-broadband MIR coherent radiation uses four-wave mixing through filamentation in air.…”
Section: Ultrafast Nir To Mir Sourcesmentioning
confidence: 99%